A fine-resolution modelling study of pollution levels in Bulgaria. Part 2: high ozone levels. (14th October 2004) - Zlatev, Zahari; Syrakov, Dimiter
Ozone pollution may cause damage to plants, animals and human beings when certain critical levels are exceeded. Therefore, it is important to study actual ozone levels and their relationship with the related emissions. Several secondary indices, directly related to the damages, are studied in this paper, rather than the proper ozone concentrations. Two versions (rough and fine grid ones) of the Danish Eulerian Model (DEM) are used in an attempt to answer the following three questions: where in Bulgaria and in Europe the highest ozone concentrations are located; how big is the influence of the European emission sources on the pollution levels in Bulgaria; and is it possible to evaluate the changes of the pollution levels in Bulgaria and in Europe when the European emissions predicted for 2010 are used? Three emission scenarios are run with meteorology for 1997: the Basic Scenario, where the 1997 EMEP emission inventory is used; the Bulgarian Scenario, where only Bulgarian emissions are set to zero; and Scenario 2010, where the 1990 EMEP inventory is modified by various factors. The results are presented by using many tables and plots, which demonstrate the relationships and the trends. Several conclusions are drawn and plans for future research are sketched.